Employing the Defective Photonic Crystal Composed of Nanocomposite Superconducting Material in Detection of Cancerous Brain Tumors Biosensor: Computational Study - C. Malek; M. Al-Dossari; S. K. Awasthi; Z. S. Matar; N. S. Abd El-Gawaad; Walied Sabra; Arafa H. Aly (Crystals, 2022)
The present research is focused on the externally tunable defect mode properties of a one dimensional (1D) defective photonic crystal (DPhC) for fast detection of cancerous brain tumors. The proposed design has utilized conventional 1D DPhC whose cavity is coated with SiO2 nanoparticles embedded in a superconducting material layer called a nanocomposite layer. The purpose of a nanocomposite superconducting layer is to induce temperature dependent external tuning of the defect mode inside PBG, in addition, to changing in the angle of incidence. The inclusion of a nanocomposite layer also improves the interaction between light and different brain tissue samples under examination. In order to investigate the transmission properties of the proposed structure the transfer matrix formulation in addition to the MATLAB computational tool has been used. First, we have chosen the optimized internal parameters at normal incidence to obtain the maximum performance of the design. Secondly, the effect of change in angle of incidence has been studied to further increase the performance by means of sensitivity, quality factor, the figure of merit and limit of detection to ensure external tuning of defect mode. After achieving a maximum value of sensitivity (4139.24 nm/RIU) corresponding to a sample containing a wall of brain tissues at θ = 63° we have further investigated the effect of change in temperature of nanocomposite layers on the position and intensity both of the defect mode inside PBG. We have found that the increase in temperature results in minute changes in sensitivity but a significant increase in the intensity of defect mode which is highly required in any photonic biosensing design. The findings of this study may be very useful for designing various bio-sensing structures which could have a significant and decisive role in the field of biomedical applications.